2015
DOI: 10.1038/cdd.2015.79
|View full text |Cite
|
Sign up to set email alerts
|

Fibril growth and seeding capacity play key roles in α-synuclein-mediated apoptotic cell death

Abstract: The role of extracellular α-synuclein (α-syn) in the initiation and the spreading of neurodegeneration in Parkinson's disease (PD) has been studied extensively over the past 10 years. However, the nature of the α-syn toxic species and the molecular mechanisms by which they may contribute to neuronal cell loss remain controversial. In this study, we show that fully characterized recombinant monomeric, fibrillar or stabilized forms of oligomeric α-syn do not trigger significant cell death when added individually… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
127
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(137 citation statements)
references
References 67 publications
6
127
1
2
Order By: Relevance
“…All known mutations associated with familial PD (A30P, E46K, H50Q, G51D, A53E, and A53T) are found in the N-terminal domain (Krüger et al, 2008; Lesage et al, 2013; Pasanen et al, 2014; Polymeropoulos et al, 1997; Proukakis et al, 2013; Zarranz et al, 2004). These mutations, with the exception of G51D, A53E, and A30P, increase the propensity of α-synuclein to form insoluble aggregates and produce morphologically distinct aggregate species (Ghosh et al, 2014; Giasson et al, 1999; Greenbaum et al, 2005; Lesage et al, 2013; Mahul-Mellier et al, 2015; Narhi et al, 1999). Though the precise mechanism by which these mutations promote aggregation has not been conclusively shown, evidence implicate an accelerated formation of oligomers (Conway et al, 2000) likely due to the destabilization of the native N-terminal conformation (Bertoncini et al, 2005a; Burré et al, 2015; Coskuner and Wise-Scira, 2013; Dettmer et al, 2015).…”
Section: α-Synuclein Structural Flexibilitymentioning
confidence: 99%
“…All known mutations associated with familial PD (A30P, E46K, H50Q, G51D, A53E, and A53T) are found in the N-terminal domain (Krüger et al, 2008; Lesage et al, 2013; Pasanen et al, 2014; Polymeropoulos et al, 1997; Proukakis et al, 2013; Zarranz et al, 2004). These mutations, with the exception of G51D, A53E, and A30P, increase the propensity of α-synuclein to form insoluble aggregates and produce morphologically distinct aggregate species (Ghosh et al, 2014; Giasson et al, 1999; Greenbaum et al, 2005; Lesage et al, 2013; Mahul-Mellier et al, 2015; Narhi et al, 1999). Though the precise mechanism by which these mutations promote aggregation has not been conclusively shown, evidence implicate an accelerated formation of oligomers (Conway et al, 2000) likely due to the destabilization of the native N-terminal conformation (Bertoncini et al, 2005a; Burré et al, 2015; Coskuner and Wise-Scira, 2013; Dettmer et al, 2015).…”
Section: α-Synuclein Structural Flexibilitymentioning
confidence: 99%
“…Based on the latter, nanoparticles, especially those that possess an ability to accelerate brillation, would be proper candidates to reduce oligomers, and consequently hinder cell death [26]. Furthermore, a recent study has suggested that the trend of brillation and aggregation process plays a crucial role in cell toxicity, and inhibiting bril growth and seeding aptitude may act as a viable strategy to protect cells from degeneration [10]. Finally, according to the existing con icts, more investigations are required to elucidate the mechanism of -Syn pathologic species and its impact on cell death while being treated by nanoparticles.…”
Section: Neurotoxicity Of Nanoliposomes and Nanoliposomes Pre-incubatmentioning
confidence: 99%
“…The degeneration of dopaminergic neuronal cells has been shown to be connected with the development of -Syn brillation [10]. Hence, there is a considerable interest in inhibiting -Syn bril formation, which can be a virtuous avenue to impede the development of PD [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Abnormal a-synuclein accumulates in glial (mainly oligodendroglial cells) and in neurons in multiple system atrophy (MSA) (Galvin et al, 2001;Jellinger, 2009;Dickson and Weller, 2011;Love et al, 2015). Oligomeric a-synuclein species are toxic (Winner et al, 2011) and abnormal a-synuclein has also the capacity of seeding thus facilitating disease progression (Angot et al, 2012;Luk et al, 2009;Mahul-Mellier et al, 2015). PD is characterized clinically by motor disturbances known as parkinsonism which are preceded by several years by sleep disorders, depression, loss of olfaction and variegated autonomic symptoms (pre-parkinsonian symptoms of PD) which continue even after the appearance of motor symptoms.…”
Section: Underlying Molecular Mechanism Of Neurodegenerative Dementiasmentioning
confidence: 98%